EFISIENSI DAN EFEKTIVITAS PENGGUNAAN MODAL KERJA PADA KOPERASI SYARIAH DI KOTA BANDA ACEH TAHUN 2011-2015 - Jauhari, Rahman; Ridwan, Ridwan (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
This study aims to analyze the efficiency and effectiveness of the use of Working Capital at Sharia Cooperative Banda Aceh city in managing by using the ratio of activity and profitability as a measuring tool, that is comparing the level of net sales with the amount of Working Capital called the ratio of working capital turnover and profit margin (Profit from financing) compared to Working Capital distributed. The research population used is 5 active Sharia cooperatives in Banda Aceh city. The type of data collected collected is secondary, items in the financial statements related to the needs of the analysis. The results showed that the average working capital turnover is very fast, reaching 70.01 times in a year, meaning the faster the turnover the shorter the turnover period of 5 days from the start of the cash invested in the components of working capital until which back into cash. The value of return on investment is rather low, namely the average performance of working capital utilization is 10.62%. This figure is quite effective but less worth the efficiency. In conclusion, there is a difference between the achievement of efficiency and effectiveness in the use of working capital where the average efficiency of the use of working capital is higher than the average working capital usage effectiveness